(3QSGdI OGeSWjhS hRjQ GdjGf (B- (3hgh jhdjGfhS (B- (3Gdedc aj GdSjGSIs - (3OGeSWjhSs
(3ChdgG (B:s
(3aCbhd Ef Gddg JHGQc hJYdi Ndb GdEfSGf Cced GdMjhGf hCJeg hLYd ajg bhi KdKG GdbhI GdYGOjI hjSejgG bhe GdTghGfjI s
(3BNQgG (B:s
(3aeYdhe Cf LejY eG hUafG Hg Gdedc jfHZi Cf jchf ai hRjQg ehLhOkG hGdSdGe JeJ hGdMeO ddg Ydi fYeg cKjQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs